CEREBRAL HEMODYNAMICS IN CHILDREN WITH LEFT VENTRICULAR FALSE TENDONS - Kuleshov, A.V.; Medrazhevskaya, Ya.A.; Malуk S.L. (World of Medicine and Biology, 2020)
Connective tissue dysplasia can be a predictor of heart arrhythmia and acute cerebrovascular disease in the future. At the moment, the question of the condition of cerebral hemodynamics in children with dysplasia is open. The purpose of the present work was to study the state of cerebral hemodynamics in children with left ventricular false tendons. The study involved 64 patients with false tendons and 23 apparently healthy children aged 13 to 17 years. Cerebral hemodynamics was assessed using rheoencephalography. In children with false tendons in the arteriae Carotis territory, the tone of large and medium-sized vessels is reduced against the background of satisfactory elasticity of their walls. Venous return is not impaired. No significant hemodynamic disorders were observed in the arteriae Vertebralis territory.